Upaya Guru dalam Membentuk Karakter Disiplin Siswa pada Masa New Normal di SMK PGRI 1 Pacitan - Eka Danik; Superi (LPPM Press, 2022)
Education is an important element in advancing world development and civilization. Educational institutions have the task of forming the character of children or students. Given the importance of character education, efforts to instill character education continue to be carried out. In the teaching and learning process, every teacher hopes that students can achieve good learning outcomes. To achieve this, it is necessary to enforce discipline for students. Discipline character is a support for student learning success. Discipline directs activities regularly, orderly, and neatly because regularity determines success in achieving learning goals and always obeys the rules that apply in the new normal period, and can control himself. This research was conducted at SMK PGRI 1 Pacitan. The type of research used by the researcher in this study is a qualitative approach which intends to understand the phenomena of what is experienced by the research subject, for example regarding behavior, perceptions, motivations, actions and others holistically and by means of descriptions in the form of words and language. . The results showed that 1). Teachers become role models for their students in learning. 2). Teachers always actively remind students about the importance of discipline and maintaining health. 3.) The teacher gives sanctions to students who commit violations.